Employee turnover likelihood and earnings management : evidence from the inevitable disclosure doctrine - Gao, Huasheng (2019)
We present evidence that managers consider employee turnover likelihood in their accounting choices. Our tests exploit U.S. state courts’ staggered recognition of the inevitable disclosure doctrine (IDD), which reduces employees’ ability to switch employers. We find a significant decrease in upward earnings management for firms headquartered in states that recognize the IDD, relative to firms headquartered elsewhere. The effect of the IDD is stronger for firms relying more on human capital and for firms whose employees have higher ex-ante turnover likelihood, confirming the employee retention channel. Overall, our results support the view that retaining employees is an important motive for corporate earnings management.